A method of protecting information in cyber-physical space - Dzheniuk, Nataliia; Yevseiev, Serhii; Lazurenko, Bogdan; Serkov, Oleksandr; Kasilov, Oleg (Національний технічний університет "Харківський політехнічний інститут", 2023)
The subject of the study is the processes of ensuring the reliability and security of information in cyber-physical space. The objective is to develop recommendations for the implementation of a method of information security in cyber-physical space. The development is based on the technology of ultra-wideband signals circulating in wireless communication channels. The task is to ensure the stable and reliable operation of the airborne wireless mobile communication network, which is the main component of cyberspace and its most vulnerable link to destructive influences. Methods used: methods of analytical modelling and time-position pulse coding. The following results were obtained. It is shown that in order to ensure high quality of wireless network operation, it is necessary to expand its bandwidth, which is limited by the physical resource of the radio frequency spectrum. It is proposed to overcome this contradiction by applying the technology of ultra-wideband signals, the base of which is much larger than one. In this case, the information signal is emitted without a carrier frequency simultaneously in the entire frequency band, provided that the signal level is lower than the noise level. The method of positional-time coding is used, in which each information bit is encoded by hundreds of ultra-short chip pulses arriving in a certain sequence. In such wireless communication systems, the use of autocorrelation reception of modulated ultra-wideband signals is proposed. A comparative analysis has shown that the wireless network with the best reliability and noise immunity is the one where the time separation of the reference and information signals is applied. During the first half of the bit interval, the switch closes the transmitter output directly to the ultra-wideband signal generator, forming a reference signal. In the middle of the bit interval, the switcher switches the output to one of two possible positions depending on the signal "zero" or "one", forming the information part of the signal. Conclusions. Systems with autocorrelation reception and separate transmission of reference and information signals provide a high level of structural signal concealment, as well as reliable transmission of digital information, especially in conditions of interference.

Предметом дослідження є процеси забезпечення надійності та безпеки інформації в кіберфізичному просторі. Мета – розробити рекомендації щодо впровадження методу захисту інформації в кіберфізичному просторі. В основі розробки лежить технологія надширокосмугових сигналів, що циркулюють по бездротових каналах зв'язку. Завдання полягає в тому, щоб забезпечити стабільну та надійну роботу мережі бездротового мобільного повітряного зв'язку, яка є основною складовою кіберпростору та його найбільш вразливою ланкою до дестабілізуючих впливів. Використані методи: методи аналітичного моделювання та часопозиційного імпульсного кодування. Були отримані наступні результати. Показано, що для забезпечення високої якості роботи бездротової мережі необхідно розширити її смугу пропускання, яка обмежена фізичним ресурсом радіочастотного спектру. Це протиріччя вирішується застосуванням технології надширокосмугових сигналів, база яких набагато більша за одиницю, при цьому інформаційний сигнал випромінюється без несучої частоти одночасно у всій смузі частот за умови, що рівень сигналу нижче шуму. рівень. У цьому випадку використовується метод позиційно-часового кодування, при якому кожен біт інформації кодується сотнями надкоротких імпульсів-чіпів, які подаються в певній послідовності. У таких бездротових системах зв'язку пропонується використовувати автокореляційний прийом модульованих надширокосмугових сигналів. Порівняльний аналіз показав, що найкраща надійність і завадостійкість досягається в бездротовій мережі, де використовується часове розділення опорного та інформаційного сигналів. Таким чином, протягом першої половини бітового інтервалу комутатор закриває вихід передавача безпосередньо на генератор надширокосмугового сигналу, формуючи опорний сигнал. У середині бітового інтервалу комутатор перемикає вихід в одне з двох можливих положень в залежності від сигналу "нуль" або "одиниця", формуючи інформаційну частину сигналу. Висновки. Системи з автокореляційним прийомом і роздільною передачею опорного та інформаційного сигналів забезпечують високий рівень приховування структурного сигналу, а також надійну передачу цифрової інформації, особливо за наявності перешкод.
Спосіб захисту інформації в кіберфізичному просторі
Keywords: cyberphysical space; cybersecurity; ultra-wideband signal technology; mobile wireless network; кіберфізичний простір; кібербезпека; технологія ультраширокосмугового сигналу; мобільна бездротова мережа